Prevalence of Cerebellar Ataxia in Patients with Hypothyroidism - Irfana, Aneel Kumar, Iqra Kokhar, Aftab Shah, Imdad Ali Ansari, Bashir Ahmed Shaikh (Pakistan Journal of Medical & Health Sciences, 2023)
Objectives: To determine the prevalence of cerebellar Ataxia in patients with hypothyroidism. Materials and Methods: The design of this study was cross sectional study design and this study was conducted in Shaheed Mohtarma Benazir Bhutto Medical University, Larkana. This study was conducted in the duration of 6 months from July 2022–Dec 2022. Total 13 patients with hypothyroidism were enrolled. Routine blood investigation and Thyroid Function Tests were done for all patients. MRI was done for all patients in order to rule out demyelinating, vascular and structural causes of cerebellar ataxia. All the data was collected in predesigned questioner. Results: A total of 13 patients with mean age of 50.92±11.21 years were enrolled. Out of total, 69.2% patients were male and 30.8% patients were female. Clinical characteristics of enrolled patients are given in table 1-0. The mean and SD value of T3, T4 and TSH were 50.9±11.21, 2.80±0.63 and 77.30±10.57 respectively. The TPO antibodies test were performed that shows mean value of 31.15±3.38, that fall in normal range. And MRI brain was also normal. Distribution of patients on the basis of Ataxia was done and it was found that 4 (30.8%) had ataxia. Practical implication: This study will help the clinical practitioner to keep in mind that there is chance of ataxia in patients suffering from hypothyroidism. So the clinical practitioner should take care of the patients to avoid such complication. There is evidence that the ataxia has been reversed by thyroid replacement therapy. Conclusion: It is concluded that Hypothyroidism is responsible to cause cerebellar ataxia. Therefore early treatment should be taken to avoid this manifestation. Keywords: Cerebellar Ataxia, hypothyroidism, Thyroid Function Tests